PUSAKA BUDAYA KAWASAN PESISIR: TINJAUAN ARKEOLOGIS ATAS POTENSI DI KEPULAUAN MALUKU - Marlon Ririmasse (Badan Riset dan Inovasi Nasional, 2015)
The coastal area has long been the major domain in the review of the world cultural history. The distinctive geographical character has made this region a starting point for the process of contact and interaction between cultures. As the world’s largest archipelago, Indonesia is one of the countries with the longest coast lines; a situation that reflects the colossal potential of the coastal region, not only politically and economically, but culturally as well. As one of the largest archipelagoes in Indonesia, the Moluccas also has the same potency. This paper tries to identify potential cultural heritage of coastal areas in the Maluku Archipelago from the archeological perspective and creates the discussion sphere to develop the management approach. Reconnaissance survey and literature study have been chosen as the approach in this research. This study found that the Maluku region has a great potency of cultural heritage of coastal areas that need to be managed with a sustainable development approach. Kawasan pesisir sejak lama telah menjadi salah satu tema utama dalam tinjauan sejarah budaya dunia. Karakter geografisnya yang khas, membuat wilayah ini menjadi titik mula bagi proses kontak dan interaksi antar budaya. Hadir sebagai kepulauan terbesar di dunia, Indonesia menjadi salah satu negara dengan garis pantai terpanjang. Suatu keadaan yang mencerminkan potensi kolosal kawasan pesisir di negeri ini. Termasuk potensi secara kultural. Sebagai salah satu kepulauan terluas di Indonesia, Maluku juga kaya dengan pusaka budaya kawasan pesisir. Makalah ini merupakan langkah awal untuk menemukan dan mengenali potensi pusaka budaya kawasan pesisir yang ada di Kepulauan Maluku dari sudut pandang studi arkeologi serta membuka ruang diskusi bagi arah pengelolaannya. Survei penjajakan dan studi pustaka dipilih sebagai pendekatan dalam kajian. Hasil penelitian menemukan bahwa wilayah Maluku memiliki potensi besar pusaka budaya kawasan pesisir yang perlu dikelola dengan pendekatan pengembangan berkelanjutan.